Solitary wave solutions of the Vakhnenko–Parkes equation - Majid, Fayequa; Triki, Houria; Hayat, Tasawar; Aldossary, Omar M. M.; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2012)
In this paper, two solitary wave solutions are obtained for the Vakhnenko–Parkes equation with power law nonlinearity by the ansatz method. Both topological as well as non-topological solitary wave solutions are obtained. The parameter regimes, for the existence of solitary waves, are identified during the derivation of the solution.